Differential Expression of GNAS and KRAS Mutations in Pancreatic Cysts - Lee, Linda S; Doyle, Leona A; Houghton, Jeffrey; Sah, Sachin; Bellizzi, Andrew M; Szafranska-Schwarzbach, Anna E; Conner, James R; Kadiyala, Vivek; Suleiman, Shadeah L; Banks, Peter A; et al. (JOP. Journal of the Pancreas, 2014)
Context KRAS mutations play an important role in pancreatic cancer. GNAS mutations were discovered in intraductal papillary mucinous neoplasms (IPMN). Objectives Our aim was to identify the frequency of KRAS and GNAS mutations in pancreatic cystic neoplasms and pancreatic ductal adenocarcinoma (PDAC). Methods Sixty-eight surgically resected formalin fixed, paraffin embedded pancreatic specimens were analyzed, including: 1) benign (20 serous cystadenoma (SCA)), 2) pre-malignant (10 mucinous cystic neoplasm (MCN), 10 branch duct intraductal papillary mucinous neoplasm (BD-IPMN), 9 main duct IPMN (MD-IPMN)), 3) malignant (19 PDAC). Total nucleic acid extraction was performed. KRAS codon 12/13 and GNAS codon 201 mutations were interrogated via targeted sequencing using the Ion Torrent’s Personal Genome Machine (PGM). Results Mean age of 68 patients was 61.9±8.4 with 72% female. KRAS and GNAS mutations were more common in PDAC and IPMN. KRAS mutations predominated in PDAC compared to pancreatic cysts (16/19, 84% versus 10/49, 20%; P<0.001). GNAS mutations were more common in IPMN compared to non-IPMN lesions (8/19, 42% versus 2/49, 4%; P=0.0003). No GNAS mutations were detected in PDAC and MCN while 2 SCA carried GNAS mutations. Double mutations with KRAS and GNAS were only present in IPMN (5/19 versus 0/30 SCA and MCN, P=0.006). Conclusions KRAS and GNAS mutations were more common in PDAC and IPMN with KRAS mutations primarily in PDAC and GNAS mutations more frequent in IPMN. No GNAS mutations occurred in MCN and double mutations were only present in IPMN. Image: Serous cystadenoma with microcysts lined by bland cuboidal epithelium.